2013
DOI: 10.1038/nature12302
|View full text |Cite
|
Sign up to set email alerts
|

Unusual base pairing during the decoding of a stop codon by the ribosome

Abstract: During normal translation, binding of a release factor to one of the three stop codons (UGA, UAA or UAG) results in termination of protein synthesis. However, modification of the initial uridine to a pseudouridine (Ψ) allows efficient recognition and read-through of these stop codons by a transfer RNA (tRNA), although it requires formation of two normally forbidden purine-purine base pairs1. We have determined the crystal structure at 3.1 Å resolution of the 30S ribosomal subunit in complex with the anticodon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
134
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(145 citation statements)
references
References 19 publications
8
134
0
3
Order By: Relevance
“…Similarly, C was found to be widely present in mRNA and change in response to environmental signals, including starvation and heat shock in yeast and serum starvation in human cells [43][44][45]. How these modifications influence mRNP biogenesis and the gene expression program at large remains to be seen, but it is interesting to consider RNA modification as another means of altering the genetic code, the effect of which can be dramatic given the reported ability of C to alter decoding of stop codons [49,50].…”
Section: A Role For Rna Modificationmentioning
confidence: 96%
“…Similarly, C was found to be widely present in mRNA and change in response to environmental signals, including starvation and heat shock in yeast and serum starvation in human cells [43][44][45]. How these modifications influence mRNP biogenesis and the gene expression program at large remains to be seen, but it is interesting to consider RNA modification as another means of altering the genetic code, the effect of which can be dramatic given the reported ability of C to alter decoding of stop codons [49,50].…”
Section: A Role For Rna Modificationmentioning
confidence: 96%
“…Artificially targeted pseudouridylation of stop codons in vivo leads to noncanonical base pairing of Ψ in the decoding center of the ribosome and efficient nonsense suppression (Karijolich & Yu, 2011). Structural studies of this surprising phenomenon suggested the possibility of more widespread effects of pseudouridine on decoding (Fernández et al, 2013).…”
Section: Rna Modificationsmentioning
confidence: 97%
“…Em condições normais, este processo ocorre com três códons de parada diferentes, UGA, UAA ou UAG (Fernández et al, 2013).…”
Section: Mecanismos Envolvidos Na Síntese Proteicaunclassified